Environmental Influences on Sheriff Perceptions and Strategies - Hancock, Katy (International Journal of Criminology and Sociology, 2019)
Scholars generally agree that law enforcement organizations are influenced by the environment. While most research on criminal justice organizations has focused on municipal law enforcement agencies, sheriff agencies are distinct from municipal police agencies for a variety of reasons. As such, sheriff agencies may be uniquely impacted by environmental pressures. In the current study, electronic surveys were sent to sheriffs in 9 states to assess their concern about juvenile trafficking, their perception of environmental groups’ concern, and the agency’s response to juvenile trafficking. Results suggested a complex relationship between environmental groups, respondent perceptions, and agency response. Most notably, sheriffs seemed to view themselves as most in sync with local groups, especially the community. Additionally, rural agencies did seem to be influenced differently by environmental groups than urban and suburban agencies. Future research should study rural agencies and also seek to more deeply understand the complex relationships between the environment and sheriffs.